Potential Approaches Versus Approved or Developing Chronic Myeloid Leukemia Therapy - Andretta, Emanuela; Costa, Caterina; Longobardi, Consiglia; Damiano, Sara; Giordano, Antonio; Pagnini, Francesco; Montagnaro, Serena; Quintiliani, Massimiliano; Lauritano, Chiara; Ciarcia, Roberto (Frontiers in Oncology, 2021)
Tyrosine kinase inhibitors (TKIs) have revolutionized the treatment of patients with chronic myeloid leukemia (CML). However, continued use of these inhibitors has contributed to the increase in clinical resistance and the persistence of resistant leukemic stem cells (LSCs). So, there is an urgent need to introduce additional targeted and selective therapies to eradicate quiescent LSCs, and to avoid the relapse and disease progression. Here, we focused on emerging BCR-ABL targeted and non-BCR-ABL targeted drugs employed in clinical trials and on alternative CML treatments, including antioxidants, oncolytic virus, engineered exosomes, and natural products obtained from marine organisms that could pave the way for new therapeutic approaches for CML patients.